(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Water aging is one of the causes of fiber-reinforced thermoplastic (FRTP) degradation during long-term service. It affects not only the mechanical properties of FRTPs, but also their erosion by solid particles. However, little research has been done on the effects of water aging on the erosion of FRTPs. The aim of this research was to study the effects of hot water absorption and desorption on the solid particle erosion of carbon-fiber-reinforced poly (ethylene terephthalate) (PET) composites. It was found that the PET-based composite erosion rate increased with increasing immersion time and decreased after redrying, whereas, the PET resin erosion rate decreased after hot water treatment. These effects depended on changes in the resin/fiber interfacial strength. Changes in the interfacial strength were investigated using short beam shear tests and dynamic mechanical analysis. It can be found that the interlaminar shear strength of the composite decreased sharply after hot water treatment based on the results of short beam shear tests and the storage modulus and glass-transition temperature decreased after hot water treatment according to the results of dynamic mechanical analysis.